The fast and the furriest - Ryan, Sofie, 1958- (Ryan, Sofie, 1958- Second Chance cat mystery, 2018)
Sarah Grayson owns Second Chance, a shop that sells lovingly refurbished items in the charming town of North Harbor, Maine. But she couldn't run the store without the help of her right-hand man, Mac - or her dashing rescue cat, Elvis. Mac's life before North Harbor was always a little mysterious, but it becomes a lot more intriguing when a woman from his past shows up in town... and then turns up dead. Suspicion falls on Mac, but Sarah - and Elivs - know he can't be the killer, and they hope they can prove his innocence quick as a whisper.